L’IMPACT DES FACTEURS ENVIRONNEMENTAUX SUR L’INTERNATIONALISATION DES FRANCHISES MAROCAINES - AMAZIAN MOUNIA; BENABDELKRIM EL FILALI YASMINE (Revue Marocaine de Recherche en Management et Marketing, 2022)
The objective of this work is to initiate research on franchising in Morocco. It focuses on the internationalization of Moroccan franchise networks, both international Moroccan networks and domestic networks that intend to internationalize in the coming years. It focuses on measuring the factors influencing the intention to internationalize by Moroccan franchisors. The objective is to analyze the environmental factors that explain the intention to internationalize by Moroccan franchisors. To do this, A survey conducted to 43 managers of international development of Moroccan franchise networks revealed that 30% of Moroccan networks are already present abroad are considering new locations, and 70% of the networks active on the national territory alone wish to go abroad in the next few years. Using the discriminant analysis method, this research highlights the influence of institutions and external agents on the intention to internationalize of Moroccan franchisors.